2019
DOI: 10.3889/oamjms.2019.167
|View full text |Cite
|
Sign up to set email alerts
|

High Fetuin-A Level as a Protective Factor to Abdominal Aortic Calcification in Indonesian Regular Hemodialysis Patients

Abstract: BACKGROUND: Although the prevalence of cardiovascular disease decreases in the general population, this pattern is not followed in hemodialysis patients. Hence cardiovascular events still occur in 50% of cases resulting in hemodialysis patients. One of the risk factors is vascular calcification. The pathogenesis is not yet fully understood, but recent years studies have shown that vascular calcification in chronic kidney disease (CKD) occurs as a result of the interaction of stimulatory and inhibitory factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Data from the Indonesian Renal Registry (2017) shows that hypertension is still the most common comorbid disease in CKD patients undergoing hemodialysis in Indonesia with (36%) and followed by diabetes (29%) [11]. This study is also consistent with study conducted by Muzasti et al in 2018 in Medan, Indonesia, where the majority of subjects who experienced CKD were men as many as 61.8% and also suffering from comorbid hypertension by 75% [12]. In line with this study, hypertension is the most common disease suffered by 51 respondents (71.8%) and DM in 13 respondents (18.3%).…”
Section: Discussionsupporting
confidence: 84%
“…Data from the Indonesian Renal Registry (2017) shows that hypertension is still the most common comorbid disease in CKD patients undergoing hemodialysis in Indonesia with (36%) and followed by diabetes (29%) [11]. This study is also consistent with study conducted by Muzasti et al in 2018 in Medan, Indonesia, where the majority of subjects who experienced CKD were men as many as 61.8% and also suffering from comorbid hypertension by 75% [12]. In line with this study, hypertension is the most common disease suffered by 51 respondents (71.8%) and DM in 13 respondents (18.3%).…”
Section: Discussionsupporting
confidence: 84%
“…Based on this, our study found that higher testosterone levels were bene cial in reducing AAC. Age is an important risk factor for vascular calci cation, and the risk of AAC increases with age [32][33][34]. In a further subgroup analysis, we also found that the protective effect of testosterone was more pronounced in older age groups (Age group = 63-79).…”
Section: Discussionsupporting
confidence: 62%
“…Different from Fetuin-A, which acts as a protective factor to abdominal aortic calcification, [ 24 ] the pathogenesis of correlation between FGF23 and abdominal aortic calcification was remained unclear. Vascular smooth muscle cells' (VSMC) transdifferentiation into osteoblast-like cells was an essential mechanism of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%